2018
DOI: 10.1155/2018/1026237
|View full text |Cite
|
Sign up to set email alerts
|

Humification and Humic Acid Composition of Suspended Soil in Oligotrophous Environments in South Vietnam

Abstract: Humification is considered to be a global process that is implemented in soils and organic sediments and also in natural water and air. e term "suspended soils" has become increasingly common in recent years. Suspended soils are defined as the part of the organic matter that has not undergone the full decomposition process and has not turned into the humus of terrestrial soils. Suspended soils were shown to contain higher total nitrogen, phosphorus, and potassium contents than the forest soil, but the moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This was due to the erosion of carbonate rocks in the middle course of the Lena River; the presence of carbonates was also noted in the ridges adjacent to the delta [43]. In the studied soils, relatively little SOM accumulated, with the highest content noted in the wind shelter site, which was associated with more favorable conditions for humification [44]. The enrichment of organic matter with nitrogen is low, according to Orlov [45].…”
Section: The Physico-chemical Characteristics Of Study Soilsmentioning
confidence: 74%
See 1 more Smart Citation
“…This was due to the erosion of carbonate rocks in the middle course of the Lena River; the presence of carbonates was also noted in the ridges adjacent to the delta [43]. In the studied soils, relatively little SOM accumulated, with the highest content noted in the wind shelter site, which was associated with more favorable conditions for humification [44]. The enrichment of organic matter with nitrogen is low, according to Orlov [45].…”
Section: The Physico-chemical Characteristics Of Study Soilsmentioning
confidence: 74%
“…From the data obtained, we noted that the most humified remains were formed in buried organic remains (numbers 6, 2, 8). The increased proportion of aromatic substances was associated with local position in the relief, the duration of the humification process, wind conditions, hydromorphism of the territory and the precursors of humification (vegetation) [44]. According to degradation hypotheses, stable plant and microbial biopolymers, during transformation, form aromatic benzene rings and labile aliphatic fragments are almost completely mineralized.…”
Section: The Stabilization Of Organic Matter Based On 13 C Nmr Spectroscopymentioning
confidence: 99%
“…These findings indicate that the crown nutrition cycle and epiphytic nutrition are largely separate from wood litter [ 4 ]. By contrast, our previous studies have suggested that complete humification processes do occur in suspended soils [ 11 , 12 ]. Therefore, the edaphic role of epiphytic substrates remains underestimated.…”
Section: Introductionmentioning
confidence: 72%
“…On degradation, the lignin-derived aromatic C contributes to a humic fraction of SOM (humification), which is core to soil fertility ( Fuchs et al., 2011 ). Abakumov et al. (2018) suggest that humification processes supplemented by organic inputs application boosts SOM.…”
Section: Resultsmentioning
confidence: 99%